Pancreatic enzymes digest obstructive meconium from cystic fibrosis pig intestines - Gangadharan Nambiar, Gopinathan; Gonzalez Szachowicz, Sussette; Zirbes, Christian F.; Hill, Jared J.; Powers, Linda S.; Meyerholz, David K.; Thornell, Ian M.; Stoltz, David A.; Fischer, Anthony J. (Frontiers in Pediatrics, 2024)
Meconium ileus (MI) is a life-threatening obstruction of the intestines affecting ~15% of newborns with cystic fibrosis (CF). Current medical treatments for MI often fail, requiring surgical intervention. MI typically occurs in newborns with pancreatic insufficiency from CF.Meconium contains mucin glycoprotein, a potential substrate for pancreatic enzymes or mucolytics. Our study aim was to determine whether pancreatic enzymes in combination with mucolytic treatments dissolve obstructive meconium using the CF pig model. We collected meconium from CF pigs at birth and submerged it in solutions with and without pancreatic enzymes, including normal saline, 7% hypertonic saline, and the reducing agents Nacetylcysteine (NAC) and dithiothreitol (DTT). We digested meconium at 37 °C with agitation, and measured meconium pigment release by spectrophotometry and residual meconium solids by filtration. In CF pigs, meconium appeared as a solid pigmented mass obstructing the ileum.Meconium microscopically contained mucus glycoprotein, cellular debris, and bile pigments.Meconium fragments released pigments with maximal absorption at 405 nm after submersion in saline over approximately 8 hours. Pancreatic enzymes significantly increased pigment release and decreased residual meconium solids. DTT did not improve meconium digestion and the acidic reducing agent NAC worsened digestion. Pancreatic enzymes digested CF meconium best at neutral pH in isotonic saline. We conclude that pancreatic enzymes digest obstructive meconium from CF pigs, while hydrating or reducing agents alone were less effective. This work suggests a potential role for pancreatic enzymes in relieving obstruction due to MI in newborns with CF.